A Pilot Trial of Applying Geographic Information System Technology to Health System Strengthening in the Upper East Region of Ghana - Eric Asuo-Mante; Abdul-Jaleel Mumuni; Myriam Asuo-Mante; Lawrence Yelifari; John Koku Awoonor-Williams; James F. Phillips (Journal of Medical Informatics and Decision Making, 2017)
Despite widespread use of Geographic Information System (GIS) technology to strengthening health systems, the application of GIS to health systems strengthening in resource-poor Sub-Saharan Africa remains rare. Over the June 2012 to December 2013 period, the Ghana Health Service (GHS) conducted a pilot application of GIS to health systems development in one rural impoverished district of the Upper East Region (UER). Workers were deployed to gather coordinates of health care facilities throughout the UER. Coordinates were linked to routine health information data, and utilized to generate maps for guiding task prioritization. For example, geocoded Community-based Management of Severe Acute Malnutrition (CMAM) program data were used to target services in communities where the prevalence of childhood acute malnutrition was relatively high. GIS was pivotal in tracking and responding to infectious disease morbidity from causes such as diarrheal diseases and tuberculosis. UER Regional Health Administration (RHA) authorities are currently utilizing GIS to map antenatal care coverage, skilled birth deliveries, neonatal mortality, still births, family planning service caseloads as well as for targeting programmatic action. Experience emerging from this trial attests to the value of GIS in contributing to efforts to strengthen health systems in rural impoverished regions of Africa.
Keywords: Ghana